Keberadaan Kesenian Reog Ponorogo Di Nagari Sungai Duo Kecamatan Sitiung Kabupaten Dharmasraya - Eka Wilya Aeksi; Afifah Asriati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The purpose of this study is to describe and reveal the existence of Reog Ponorogo art in Nagari Sungai Duo, Sitiung District, Dharmasraya Regency. This research is qualitative research with descriptive methods. The research instrument is the researcher himself and assisted by tools such as pens and cameras. Techniques of literary research, observation and interviews were used for data collection. The stages of analysis are carried out through data collection, data reduction, data presentation and conclusion drawing. The results showed that the existence of Reog Ponorogo art experienced ups and downs due to changes in its performances that made the mindset of the Nagari Sungai Duo people, especially the younger generation who were already interested in modern art and low public interest in Reog Ponorogo Art. In 1977-2013 Reog Ponorogo art existed in the midst of society, in its performances presenting mystical elements, trance and immune attractions. In 2014-2019, Reog Ponorogo's art has rarely been shown because the show does not present mystical elements which causes the audience to switch and prefer Orgen Tunggal. In 2020-2021, Reog Ponorogo Art was not displayed at all due to the Corona virus. In 2022, Reog Ponorogo Art was displayed at the event to enliven Independence Day on August 17 and a cultural parade danced as a welcome guest from the Regent of Dharmasraya on the football field. In 2023 there is another demand for Reog Ponorogo Art to be displayed at weddings.